Влияние состава и условий осаждения на структуру и свойства вакуумных композитов на основе меди, упрочненных оксидом алюминия - Зозуля, Эдуард Владимирович; Терлецкий, Александр Семенович; Меньшиков, Анатолий Григорьевич; Субботина, Валерия Валерьевна; Протасенко, Татьяна Александровна (НТУ "ХПИ", 2016)
Композиты на основе меди, упрочнённые частицами оксида алюминия, получали электронно-лучевым испарением компонентов из отдельных источников с последующим их совместным осаждением. Температуры осаждения изменялись от 293 до 673 К. Методами рентгеновской дифрактометрии и просвечивающей электронной микроскопии исследована структура композитов. Установлена смена морфологии частиц оксида алюминия при повышении температуры подложки. Рассмотрено влияние содержания и размера частиц Al₂O₃ на электрическое сопротивление, прочность и структурную стабильность при повышенных температурах. Предложены меры улучшения их свойств.

Composites obtained by electron beam evaporation components from separate sources and their subsequent co-deposition. The deposition temperatures were changed from 293 K to 673. Methods of X-ray diffraction and transmission electron microscopy were used to study the microstructure of composites strengthened by aluminum oxide particles. Composites at Al₂O₃ particle contents up to 3 vol. % were studied. Morphological change of aluminum oxide particles with increasing temperature of substrate and also at annealing was established. The particle size is closely related to phase transition. The effect of the size of particles of the oxide (Al₂O₃) and of their content on the properties of the composite has been considered, in order to optimize these characteristics. The results of this work can be used for the creation of new-generation conductors with an optimum combination of strength and electrical conductivity.
Influence of composition and deposition conditions on the structure and properties of vacuum copper-based composites strengthened by aluminum oxide
Keywords: электронно-лучевое испарение; структурная стабильность; прочность; электрическое сопротивление; structural stability; electrical resistance